Clinical Features of Infectious and Autoantibody Encephalitis - John J Millichap; J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2015)
Investigators from University of Sydney, Australia; John Radcliffe Hospital, Oxford, UK; Imperial College, London, UK; and other centers, studied infectious, immune-mediated/autoantibody associated and unknown forms of encephalitis, including frequencies, clinical and radiological phenotypes, and long-term outcome.